Connecting Environmental, Social and Governance (ESG) aspects with value creation in small and medium-sized enterprises - Aureli, Selena; Del Baldo, Mara; De Villiers, Charl (Piccola Impresa / Small Business, 2024)
Purpose. This editorial aims to examine how SMEs are transforming their way of doing business in light of social and environmental sustainability and their different approaches used to externally report ESG aspects. Design/methodology/approach. The editorial presents the contributions included in a thematic issue on ESG aspects and value creation in SMEs by framing the sustainability discourse along the « walk and talk » pathway that allows to better understand and compare what companies really do (or walk) versus what companies convey (or talk) to stakeholders. Findings. This editorial and the contributions included in the thematic issue identify some key issues that deserve future researchers’ attention when investigating SMEs’ way to ESG. First, SMEs’ approach to sustainability and circular economy may present peculiarities as they do not mimic what their larger counterparts do. Reasons for different pathways like the impact of the entrepreneur-founder’s profile and personality should be further investigated. Second, sustainability reporting in SMEs is still limited and suffers from a lack of organizational resources. In this regard, dedicated, simplified reporting standards seems to be crucial. Finally, SMEs’ walk and talk should be analysed bearing in mind their position in the value chain and network relationships that largely affects the potential for sustainability transformation and value creation. Practical and Social implications. The editorial provides some suggestion for future research and introduces the selected articles that show the walk and talk pathways to favour critical reflections useful for both managers/entrepreneurs, academic researchers and policy makers. Originality of the study. The editorial presents some concepts derived from the long-standing shared research path focusing on CSR and tries to link it to the latest ESG framework to emphasise how sustainability actions lead to value creation both in economic, social and environmental terms.